Small Group Work Learning Model for Student Engagement and Achievement in Science: Model Pembelajaran Kerja Kelompok Kecil untuk Meningkatkan Keterlibatan dan Prestasi Siswa dalam Mata Pelajaran Sains - Ani Wandira; Subhanadri; Opi Andriani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education at the primary level plays a pivotal role in shaping students’ foundational knowledge, skills, and character, yet learning engagement often remains low. Specific Background: In the context of the Merdeka Curriculum, the integrated Science and Social Studies subject (IPAS) requires active and meaningful participation, but observations at SDN 51/II Paku Aji revealed limited student involvement and poor academic results due to monotonous teaching practices. Knowledge Gap: Although cooperative learning models are widely studied, few investigations specifically address the application of Small Group Work (SGW) within the IPAS subject in elementary schools, especially regarding students’ discussion skills. Aims: This study sought to improve learning activities and outcomes of fourth-grade students through the implementation of SGW. Results: Conducted as Classroom Action Research in two cycles with 20 students, the findings showed a significant rise in teacher performance (from 77.27% to 90.90%), student participation (from 65% to 85%), and mastery of learning outcomes (from 55% to 80%). Novelty: Unlike prior studies, this research situates SGW within the Merdeka Curriculum’s integrative IPAS framework, emphasizing collaborative discussion as a core competence. Implications: The findings demonstrate that SGW not only enhances academic achievement but also fosters active engagement and social interaction, offering a practical strategy for teachers to address low participation in IPAS learning.Highlight : Teacher performance improved significantly across learning cycles. Student activity in discussion, listening, and writing increased. Mastery of learning outcomes rose from 45% to 85%. Keywords : Learning Outcomes, Student Activity, Small Group Work, IPAS, Cooperative Learning